Exploring the Characteristics of Modern Korean Buddhist Education: Focusing on the Religious Studies Lecture Notes from the Buddhist Central Seminary (Pulgyo Chungang Hangnim, 佛敎中央學林) - Eunyoung Kim (Religions)
This study examines the identity and characteristics of modern Korean Buddhist education through an analysis of the religious studies lecture notes of a student from the Buddhist Central Seminary (Pulgyo Chungang Hangnim, 佛敎中央學林), preserved at Songgwang-sa Temple. Established in 1915 and operating until 1919, the seminary introduced a significant shift from traditional scripture-centered monastic education to a modern academic system. Western and Japanese academic traditions, religious studies, philosophy, and the general educational system influenced its curriculum. The lecture notes provide insight into the adoption of modern academic disciplines within Korean Buddhist education, revealing the influence of Japanese religious studies and Western comparative religion. They also demonstrate the possibility of early introduction of religious studies as an educational field in Korea. The seminary played a dual role as a hub for national education and reflection of the colonial context, embodying the complexities of nationalism and colonial influence during Japanese occupation. This study underscores the need for further scholarly exploration to understand the multifaceted nature of modern Korean Buddhist education and its unique role within the broader historical context of East Asian Buddhist history.